Influence Of Mesh Surface Parameters In A Mechanical Cotton Seed Cleaning Unit On Cleaning Efficiency (American AgriTech: Journal of Agricultural Technology Innovation and Sustainability, 2026)
The article presents the results of experimental studies carried out on both the existing and improved Mechanical seed (cotton seed) cleaning cleaners installed in the Cotton seed sorting unit unit, aimed at increasing the cleaning efficiency of cotton seeds. Analysis of the obtained results showed that the mass of 1000 seeds increased by 1,3– 1,4 g, the impurity level decreased by 0,22–0,31%, and mechanical damage was reduced to 0,2%
Keywords: Cotton seeds; sorting; seeds